Worldly ethics : democratic politics and care for the world - Myers, Ella, 1976- (Book collections on Project MUSE., 2013)
Where most models of democratic ethics have focused on either care for the self or care for others, Ella Myers advocates an ethical approach to politics based on a collaborative care for the world.